Analysis of PDC cutter cutting‐broken conglomerate based on the discrete element method. Issue 9 (30th June 2022) - Liu, Xiaoao; Zou, Deyong; Chen, Yahui; Huang, Yong; Wang, Qing
Abstract: It is well known that the magnitude of impact load is one main reason for polycrystalline diamond compact (PDC) cutter failure rapidly when drilling conglomerate formation. However, there are many factors affecting the magnitude of impact load. To assess and mitigate these impacts, the discrete element model of PDC cutting‐broken conglomerate has been established, and the influence law of cementation strength difference (CSD), gravel diameter, and cutting velocity on impact load and gravel fragmentation in the process of cutting broken conglomerate is performed. What is more, the laboratory experiment of rock cutting by different shaped PDC cutters under different CSD and gravel diameters has also been conducted, and the correctness of numerical simulation results is verified by laboratory experiment. Meanwhile, the cutting depth and impact load of different shape PDC cutters under different CSD and gravel diameters have been analyzed. First, the simulation results show that the stripping mode of gravel mainly occurs when the CSD is large, and the corresponding axial and tangential impact load (mean axial peak cutting force [MAPCF]/mean tangential peak cutting force [MTPCF]) is relatively small. As the decrease of CSD, the gravel will be directly broken and the magnitude of the MAPCF/MTPCF will gradually increase, and the probability of impact damage to the cutting cutter will incrementally increase. In addition, larger gravel diameter and cutting velocity will lead to larger MAPCF/MTPCF, and the mode of gravel fragmentation changes gradually from being stripped to being directly broken with the increase of gravel diameter. Second, the laboratory experiment results not only verify the correctness of the simulation results but also find that ridged diamond element cutter has the smallest impact load and the largest cutting depth under different CSD and gravel diameters. This paper can provide a theoretical foundation for the optimization of drilling parameters and PDC bit design in drilling conglomerate formation. Abstract : The magnitude of impact load is one main influence factor of polycrystalline diamond compact (PDC) bit impact damage when drilling in conglomerate formation. But there are many factors affecting the magnitude of impact load. To assess and mitigate these impacts, this paper establishes the discrete element model of PDC cutting‐broken conglomerate and analyzes the effects of cementation strength difference, gravel diameter, and cutting speed on impact load. This study can provide a theoretical basis for optimizing the design of a PDC bit suitable for conglomerate formation, so as to improve the rock breaking efficiency and service life of the PDC bit.